2016
DOI: 10.1002/lno.10301
|View full text |Cite
|
Sign up to set email alerts
|

Controls on the sources and cycling of dissolved inorganic carbon in the Changjiang and Huanghe River estuaries, China: 14C and 13C studies

Abstract: The Changjiang (Yangtze River) and Huanghe (Yellow River) are the two largest rivers in China, and they transport large amounts of terrestrial carbon to the coastal waters of the East China Sea and the Bohai Sea. The sources and cycling of riverine carbon in these two large river estuaries, however, have not been well studied. In this article, we present the results of dual isotope (D 14 C and d 13 C) measurements of dissolved inorganic carbon (DIC) collected in the low reaches of the Changjiang and Huanghe an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 70 publications
6
39
0
Order By: Relevance
“…4a). This trend is consistent with higher concentrations and a more 13 C-depleted DIC signature in autumn as a consequence of OM decomposition and also terrestrially-derived groundwater DIC inputs (Hotchkiss et al 2015), while more 13 C-enriched DIC signals stem from dissolution of carbonate and siliciclastic rocks during weathering reactions in spring and winter (Wang et al 2016). The pattern of seasonal variability in d 13 C of short-chain n-FA is similar to that of the n-C 17 alkane (d 13 C 17alkane ), albeit lower in amplitude (Fig.…”
Section: Contemporary/modern Biomass Ocsupporting
confidence: 80%
See 1 more Smart Citation
“…4a). This trend is consistent with higher concentrations and a more 13 C-depleted DIC signature in autumn as a consequence of OM decomposition and also terrestrially-derived groundwater DIC inputs (Hotchkiss et al 2015), while more 13 C-enriched DIC signals stem from dissolution of carbonate and siliciclastic rocks during weathering reactions in spring and winter (Wang et al 2016). The pattern of seasonal variability in d 13 C of short-chain n-FA is similar to that of the n-C 17 alkane (d 13 C 17alkane ), albeit lower in amplitude (Fig.…”
Section: Contemporary/modern Biomass Ocsupporting
confidence: 80%
“…a). Although there are only two data point available for Δ 14 C DIC in the Yellow River (Wang et al ), higher Δ 14 C 16 + 18FA values (−2‰) and Δ 14 C DIC values (−125‰) were observed in October, while lower Δ 14 C 16 + 18FA values (−50‰) and Δ 14 C DIC values (−164‰) were evident in Spring (April). These parallel time‐series variations suggest that aquatic production is likely a source of short‐chain n ‐FAs, and hence corresponding carbon isotopic compositions of short‐chain n ‐FAs echoes that of aquatic biomass produced via photosynthetic DIC fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Since air-sea exchange likely only affects water to a depth of 80 m, DO declines after this depth because of limited inputs from oxygen-rich surface waters, and then H 2 S, CH 4 , and other dissolved gases start to accumulate, forming the chemocline (Figure 2). With the decrease of DO, DIC concentrations increase and the DIC δ 13 C and Δ 14 C values decrease (Figures 2 and 3), which are significantly different from open ocean waters and river waters (p < 0.01) ( Figures 5 and S7) Wang et al, 2012Wang et al, , 2016, but similar values have been observed in other marine cave systems (McGee et al, 2010), further suggesting a minor contribution from the atmosphere. Carbon isotopic disequilibrium between deep water in the YBH and atmospheric CO 2 or marine bicarbonate values are likely due primarily to the 13 C-depleted carbon produced by bacterial respiration (McGee et al, 2010).…”
Section: Controls On the Concentration And Isotopic Compositions Of Dicsupporting
confidence: 59%
“…The profiles of DIC concentration and isotopic compositions in the YBH indicate that the DIC in surface and deep waters are controlled by different mechanisms. The concentration and isotopic compositions of DIC in surface waters of the YBH (from 0 to 80 m) are relatively constant (Figure 3b) and very close to open ocean and estuarine values ( Figure 5), which are mainly controlled by air-sea exchange, suggesting adequate mixing of the surface waters Wang et al, 2012Wang et al, , 2016. Since air-sea exchange likely only affects water to a depth of 80 m, DO declines after this depth because of limited inputs from oxygen-rich surface waters, and then H 2 S, CH 4 , and other dissolved gases start to accumulate, forming the chemocline (Figure 2).…”
Section: Controls On the Concentration And Isotopic Compositions Of Dicmentioning
confidence: 74%
“…Bubble sizes correspond to approximate water depth. The dashed boxes indicate approximate ranges of Δ 14 C OC and δ 13 C OC values of marine OM (Blair & Aller, ; Wang et al, ) and of Yellow and Yangtze River suspended particle organic matter (SPM; Marwick et al, ; Tao et al, ; Wang et al, ). The data from Wu et al () and Kao et al () (solid symbols) are plotted without water depth information in the lower panel.…”
Section: Resultsmentioning
confidence: 99%